2007
DOI: 10.1007/s00221-006-0848-1
|View full text |Cite
|
Sign up to set email alerts
|

Motor equivalent control of the center of mass in response to support surface perturbations

Abstract: To claim that the center of mass (CM) of the body is a controlled variable of the postural system is difficult to verify experimentally. In this report, a new variant of the method of the uncontrolled manifold (UCM) hypothesis was used to evaluate CM control in response to an abrupt surface perturbation during stance. Subjects stood upright on a support surface that was displaced in the posterior direction. Support surface translations between 0.03 and 0.12 m, each lasting for 275 ms, were presented randomly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
106
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 39 publications
6
106
2
Order By: Relevance
“…Results of a recent reanalysis of support surface perturbations (Park et al 2004) also is consistent with this finding. Differences in the configuration of the joints between pre-and postperturbation phases were largely consistent with a motor equivalent response; i.e., different joint combinations between the phases achieved an equivalent CM position (Scholz et al 2007).…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…Results of a recent reanalysis of support surface perturbations (Park et al 2004) also is consistent with this finding. Differences in the configuration of the joints between pre-and postperturbation phases were largely consistent with a motor equivalent response; i.e., different joint combinations between the phases achieved an equivalent CM position (Scholz et al 2007).…”
Section: Introductionsupporting
confidence: 53%
“…Finally, two recent studies support the hypothesis that many joints along the kinematic chain are coordinated to achieve postural stability (Krishnamoorthy et al 2005;Scholz et al 2007). Krishnamoorthy et al (2005) studied joint coordination in subjects who stood as quietly as possible on a narrow beam both with and without vision.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Scholz et al 6 ) used UCM analysis to reveal that although coordination of each segment angle stabilized the COM in the sagittal plane during STS, the head and hand postions were not stabilized. Scholz et al 7 ) quantitatively showed that COM is a controlled variable of the postural system, and that its control is achieved through selective, motor equivalent changes in the joint configuration in response to support surface perturbations. The UCM analysis also revealed that the central nervous system (CNS) organizes co-variation of elemental variables to stabilize the important performance variable in a task-specific manner 8) .…”
mentioning
confidence: 99%